Western Medical Dominance and Quacks in Sri Lanka - Abeysinghe, A. (My University, 2006)
The thesis presents a sociological analysis of the position and role of quacks or medically unqualified people, who appear to play a significant part in the curative healthcare system in Sri Lanka. The study was carried out in the Ratnapura District in the Sabaragamuwa Province. Ten quacks who practice western medicine in the district and 350 patients who had sought treatment from them were selected for the study. The focus of the study is on whether the dominance of the western medical system creates the space for quacks to enter and continue as providers of western medical treatment within the healthcare delivery system in Sri Lanka. This issue was discussed paying attention to four points of view i.e., those of quacks, patients who consult quacks, formal curative healthcare services and the state. The following aspects, which were highlighted in the study as the manifestations of western medical dominance, can be considered as the factors that encouraged the quacks to enter the field of curative healthcare and continue their medical practice: 1. Marginalisation of indigenous healthcare services and the ascendancy of western healthcare services in the context of curative healthcare provision. 2. The restrictions and controls that reduced people's freedom to resort to alternative medical systems. 3. Manifestations of professional dominance in the context of the doctor-patient relationship. Besides the dominance of the western medical system, the study reveals several other social forces that have helped quacks in infiltrating the curative healthcare system and continue their practice. Firstly, quacks maintain personal relationships with health officers in the formal health sector as well as with politicians. Secondly, quacks have a 'western doctor" image among patients who consult them